Women as Breadwinners and the Transformation of Roles in the Muslim Family: Evidence from Urban South Sulawesi - Nadyatul Hikmah Shuhufi; Muh Zaitun Ardi; Fatmawati Fatmawati; Muhammad Shuhufi; Zezen Zainul Ali (Universitas Muhammadiyah Bandung, 2026)
This study examines the role of wives as family breadwinners from the perspective of normative Islam and contemporary social realities. The study employs a qualitative approach with an interdisciplinary framework that combines normative Islamic legal analysis and sociological perspectives. Primary data were collected through interviews and observations of 12 families in the Pao-Pao Permai Complex, Gowa, South Sulawesi. To date, research in Indonesia has been dominated by normative-doctrinal approaches and has not extensively examined family livelihood practices from an empirical and sociological perspective. The findings reveal four patterns of family breadwinners: (1) both husband and wife work and share financial responsibilities equally; (2) both partners work, but the wife contributes more significantly to household income; (3) the husband acts as the primary breadwinner while the wife focuses on household responsibilities; and (4) the wife becomes the sole breadwinner, particularly in single-parent households or when the husband lacks stable employment. This study demonstrates that the husband’s role as the sole provider is not an absolute theological obligation but rather a sociological phenomenon shaped by historical and social contexts. Thus, women also possess the capacity and legitimacy to assume the role of family breadwinner in accordance with contemporary socioeconomic conditions. This research contributes to the development of Islamic family law by offering a reinterpretation of the concept of maintenance based on maqāṣid al-sharī‘ah, which emphasises the welfare and justice of the family. This study affirms that a flexible division of maintenance can be justified within the framework of Islamic law, thus necessitating a more contextual approach to family law.